Avaliação dos caminhos da governança na política de compras públicas do Governo do Estado do Ceará - Silva, Alana Pinto de Macêdo da (2025)
Public procurement is one of the most transversal processes in the public sector, holding strategic value for the maintenance and fulfillment of the State's functions. With the enactment of Law No. 14,133/2021, which formalized governance in this context, federative entities had to take action to adapt to the regulatory changes. Given this scenario and the limited academic studies on public procurement with a governance focus, an interest arose in understanding the situation of the State of Ceará. This study aims to understand the implementation and meanings of procurement governance within the public procurement policy of the Government of the State of Ceará. The policy was analyzed based on the assumptions of In-Depth Evaluation, a methodology proposed and refined by Rodrigues (2008; 2011) and a group of professors from MAPP (Cruz, 2019; Gussi, 2019), which enables a broad and dense assessment, seeking understanding through historical-political processes and the perceptions of stakeholders, using a qualitative approach. Semi-structured interviews, bibliographic research, and document analysis were the techniques used for data collection (Richardson, 2017; Gil, 2021; 2024; Marconi; Lakatos, 2021). The interviews were interpreted with the support of Bardin's content analysis (2016). The results show that the implementation of procurement governance in the studied policy was strongly influenced by Results-Based Management (GpR). Moreover, the institutionalized procurement management model adheres to the rules of Law No. 14,133/2021 and aligns with it in most analyzed aspects, diverging in the guidelines for the designation of public agents for essential procurement functions. governance proved to be an evolving process that followed the improvements of the policy itself over time, with significant advancements such as the institutionalization of policies, various strategies and guidelines, the development of digital systems, and the establishment of the Annual Procurement Plan (PCA). It was also concluded that there is a diverse nderstanding of the meanings of procurement governance among the interviewees. Finally, the study identified gaps and opportunities for improvement, including the need to establish a procurement governance model, a competency-based management model, and a sustainable logistics plan; define objectives, goals, and indicators for procurement functions; and ensure adequate workforce planning for the procurement and contracting area.